A General Equilibrium Analysis of the Capital Asset Pricing Model - Harris, Richard G. (Journal of Financial and Quantitative Analysis, 1980)
The mean-variance portfolio model of Markowitz and Tobin has been the most substantive contribution to the theory of individual asset demand under uncertainty, in terms of comparative static results and testable implications. Although subject to a number of criticisms at the axiomatic level, it still stands as the classic portfolio model. The general equilibrium extension of the Tobin-Markowitz model due to Sharpe [14], Lintner [9], and Mossin [11] has led to important propositions about the nature of risk in general equilibrium and its effect on the pricing of assets, and the model has subsequently been subjected to extensive empirical testing. It has been used for a variety of purposes in areas ranging from corporate-finance theory to the debate on the social discount rate.